1999
DOI: 10.1097/00004872-199917100-00016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of different echocardiographic diagnostic criteria on the prevalence of left ventricular hypertrophy in essential hypertension

Abstract: Prevalence of echo left ventricular structural alterations among essential hypertensives seen in primary care centres in Spain ranged from 70.3 to 79.2% depending on the threshold values used. Left ventricular hypertrophy ranged from 59.2 to 72.7% and age-adjusted concentric remodelling ranged from 6.5 to 11.4% depending on the criteria used. Only one-quarter of hypertensive patients were free from morphological alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 30 publications
3
40
1
5
Order By: Relevance
“…Third, although in our series obesity was present in a lower percentage (19%) than in previous studies reporting a two/threefold higher prevalence of this phenotype, 13,23 we were able to show a large difference in LVH prevalence in the whole population as well as in the largest subgroup of overweight subjects by using the two indexation methods. The clinical relevance of this observation is that LVH should be identified by adjusting LVM to height not only in obese but also in overweight hypertensive individuals.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Third, although in our series obesity was present in a lower percentage (19%) than in previous studies reporting a two/threefold higher prevalence of this phenotype, 13,23 we were able to show a large difference in LVH prevalence in the whole population as well as in the largest subgroup of overweight subjects by using the two indexation methods. The clinical relevance of this observation is that LVH should be identified by adjusting LVM to height not only in obese but also in overweight hypertensive individuals.…”
Section: Discussioncontrasting
confidence: 80%
“…22 In the VITAE Study (Ventriculo Izquierdo Tension Arterial Espana) including 946 essential hypertensives (53.3% women, 45% obese) from primary care centres, LVH prevalence ranged from 59.2% by indexing to BSA (that is, LVMI X111/102 g m À2 ) to 70.7% by indexing to height (that is, LVMI X50/ 47 g m À2.7 ). 23 In the Gubbio Population Study, a clinical survey performed in a small Italian town, the prevalence of LVH among 250 hypertensive patients was nearly twofold higher (43.6 vs 24.0%) when LVM was indexed to height (that is, LVMI 49.2/46.7 g m À2.7 ) compared to BSA indexation (that is, 116/104 g m À2 ). 24 Although these and other studies 13,25 have shown that indexation of LVM to height raised to its allometric power yields the highest prevalence of LVH, no data are provided about the classification of subjects according to BMI categories, as performed in the present report.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Our values, however, are in line with that reported (70%) in a large Spanish survey of 946 essential hypertensives from primary care centres. 31 Several factors may explain the high prevalence of LVH in our survey: (1) old age (less than 7% of our patients were o40 years); (2) duration of hypertension (less than 20% were untreated, that is, in the initial phase); moreover, up to 50% of patients had a previous echo examination and was reassessed for LVH regression; (3) non-standardized identification of LV interfaces due to the lack of a reading centre. This latter methodological aspect could be in part responsible for large differences in LVH prevalence seen among the centres.…”
Section: Echocardiography In Hypertension C Cuspidi Et Almentioning
confidence: 99%
“…To date, only few surveys have assessed the impact of different echocardiographic diagnostic criteria on the prevalence of LVH in a representative populationbased sample of essential hypertensives. Coca et al 29 investigated 946 hypertensive patients seen in primary care centres, using three cut off values, and found that LVH mass was present in 58% to 72% of subjects.…”
Section: Echocardiography In Hypertensive Patients: When and How?mentioning
confidence: 99%